Cisplatin versus Cetuximab Given Concurrently with Definitive Radiation Therapy for Locally Advanced Head and Neck Squamous Cell Carcinoma - Ley, Jessica (2013)
OBJECTIVE: Whether or not cisplatin and cetuximab are similarly effective in improving outcomes when added to radiation therapy(RT) in HNSCC is unknown. METHODS: Retrospective analysis of patients treated with definitive RT and cisplatin(n=18) or cetuximab(n=29). RESULTS: T and N classifications, stage, HPV status, and smoking history were balanced in the two groups; however, patients in the cisplatin group were younger, and had better performance status. Delivery of RT was similar between the two groups. Median follow-up was 23(4–64) months. Disease-specific(DSS) survival at 3 years was 83% in the cisplatin group and 31% in the cetuximab group. Recurrent disease was more common in the cetuximab group compared with the cisplatin group(17 versus 4 patients). Propensity score analysis to adjust for differences in patient characteristics which influenced treatment selection showed that DSS was indeed longer with cisplatin than with cetuximab(DSS Hazard Ratio[HR] 0.15{Confidence Interval[CI]0.033,0.66},p=0.012). CONCLUSIONS: DSS was superior in the patients given cisplatin with definitive RT compared to cetuximab with definitive RT due to a lower risk of recurrent disease in the cisplatin group. These observations could not be explained by differences between the two groups in the patient and tumor characteristics or in treatment delivery.